THE PLACE OF THE SCIENTIFIC HERITAGE OF IMAM AT THERMIZY IN THE DEVELOPMENT OF MOVAROUNNAHR SCIENCE - Alijonova daughter of Gulnazakhan Mohammad; Kahhorova Zilola Rustam's daughter (European Science Publishing, 2024)
This article analyzes the role and importance of Imam al-Tirmizi's scientific heritage in Movarounnahr. Imam at-Tirmidhi is one of the great scholars who made a great contribution to the development of hadith science in Islam. His works, methodological approach and scientific thinking influenced the development of religious and scientific thinking in Movarounnahr. The article examines how Imam al-Tirmidhi and his scientific legacy are perceived in his time and today.
Keywords: Uzbek: Imam al-Tirmizi, scientific heritage, Movarounnahr, Islamic philosophy, hadith science.